The Impact of Minimally-Invasive open Donor Hepatectomy on Outcomes in Adult Living Donor Liver Transplantation. (July 2018) - Soejima, Yuji; Yoshizumi, Tomoharu; Ikegami, Toru; Harada, Noboru; Ito, Shinji; Toshima, Takeo; Motomura, Takashi; Mano, Yohei; Ohira, Masashi; Maehara, Yoshihiko
Abstract : Aim: Technical problems in adult living donor liver transplantation (LDLT) has been almost overcome, which resulted in recent improvement of recipient outcomes for most centers. However, the outcome of minimally-invasive donor hepatectomy (MIDH) has not been well established. In this study, we evaluate the impact of MIDH on the outcomes through our 20-year LDLT experience. Methods: Six hundred and four adult living donors were included in the study, after excluding donors with left lateral segment (n=64), S2-monosegment (n=3) and posterior segment (n=12) grafts. MIDH using a minimal upper midline incision was introduced since August 2012 and exclusively used since then. Various clinical parameters of MIDH (n=188) were compared with those of conventional donor hepatectomy (CDH, n=417). Results: The mean wound length of the MIDH group was 13.3±2.2cm. Right lobe grafts were more often utilized in the MIDH group as compared to the MIDH group (34.8% vs. 58.0%, p<0.0001). Operative time (430±105 vs. 297±61 min, p<0.0001) and blood loss (538±404 vs. 295±254ml, p<0.0001) were significantly less in the MIDH group. Postoperative liver function tests including peak Total bilirubin (2.5±1.4 vs. 2.1±1.0mg/dl, p=0.0001) and peak ALT (525±275 vs. 481±246IU/L, p<0.05) were significantly better in the MIDH group. Furthermore, incidence of overall complications (25.6 vs. 5.9%, p<0.0001) and Clavien 3⩽ complications (7.4 vs. 2.1%, p<0.0001) were markedly reduced in the MIDH group. Accordingly, the length of postoperative hospital stay (14.0±7.5 vs. 9.0±7.9days, p<0.0001) was significantly shorter in the MIDH group. There was neither intraoperative autologous transfusion, nor irreversible disability as well as mortality experienced throughout the period. Conclusion: MIDH is safe and should be the standard procedure in adult LDLT. Further study which compares MIDH with laparoscopic donor hepatectomy is warranted in the near future.